2017
DOI: 10.1007/s13197-017-2772-8
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa butter symmetrical monounsaturated triacylglycerols: separation by solvent fractionation and application as crystallization modifier

Abstract: Symmetrical monounsaturated triacylglycerols-also known as SUS (saturated unsaturated saturated triacylglycerols)-are the main triacylglycerols present in cocoa butter (CB), exhibiting decisive influence in the tempering process conditions and sensorial characteristics in chocolate products. CBs with lower amounts of SUS do not crystallize adequately in chocolate processing, generating a low quality product with higher susceptibility to fat bloom formation. In this context, fractions with higher contents of SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Both CB and CBE are composed primarily of POP, POSt and StOSt, with respective concentrations for CB of 16.45%, 40.30% and 23.66% (total 80.41%) and for CBE of 25.04%, 9.29% and 43.47% (total 77.8%), with total values lower than the range found in the literature for CBE (79.6 to 85.7%) (BOOTELLO et al, 2012) and for CB (87.7 to 91.7%) (RIBEIRO et al, 2012;BUSCATO;KIECKBUSCH, 2017). The important characteristic of this CBE is the high amount of StOSt compared to other CBE studied before (DE CLERCQ et al, 2017).…”
Section: Crystallization Study Of Cb:cbe Blends: Chemical Compositionmentioning
confidence: 55%
See 1 more Smart Citation
“…Both CB and CBE are composed primarily of POP, POSt and StOSt, with respective concentrations for CB of 16.45%, 40.30% and 23.66% (total 80.41%) and for CBE of 25.04%, 9.29% and 43.47% (total 77.8%), with total values lower than the range found in the literature for CBE (79.6 to 85.7%) (BOOTELLO et al, 2012) and for CB (87.7 to 91.7%) (RIBEIRO et al, 2012;BUSCATO;KIECKBUSCH, 2017). The important characteristic of this CBE is the high amount of StOSt compared to other CBE studied before (DE CLERCQ et al, 2017).…”
Section: Crystallization Study Of Cb:cbe Blends: Chemical Compositionmentioning
confidence: 55%
“…These results confirm that when there are no differences in the fat blends physical properties the replacement of a CB for CBE on those amounts do not interfere in the chocolate quality either. Besides that the use of CBE is advantage due the presence of higher amounts of StOSt triacylglycerols that can strengthen the development of β crystals in the tempering process-desirable in the chocolate production and also inhibit the formation of fat bloom during chocolate storage (BUSCATO; GRIMALDI; KIECKBUSCH, 2017). As found in a previous work for the same chocolate composition after temperature cycling 20/33 °C (DA SILVA; GRIMALDI; GONÇALVES, 2017).…”
Section: Cb:cbe Blends In Chocolatementioning
confidence: 62%
“…PKO shows a high amount of trilaurin and other TAGs composed of completely saturated fatty acids, whereas AMF and CB contain high amount of monounsaturated TAGs. 44–46 Previous studies have shown that small amounts of monounsaturated TAGs lead to the formation of rough crystallite surfaces, whereas completely saturated TAGs form smooth surfaces. 47 Hence, the saturated TAGs present in PKO form crystallites with smooth surfaces thereby reducing crystallite cluster and floc adhesion strength.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular origin determining the crystallite cluster and floc strength is related to the TAG composition. PKO shows a high amount of trilaurin and other TAGs composed of completely saturated fatty acids, whereas AMF and CB contain high amount of monounsaturated TAGs [44][45][46] . Previous studies have shown that small amounts of monounsaturated TAGs lead to the formation of rough crystallite surfaces, whereas completely saturated TAGs form smooth surfaces 47 .…”
Section: Crystal Microstructure Of Tag Cmsmentioning
confidence: 99%
“…Theobroma cacao is cultivated in Ivory Coast, Nigeria, Ghana, Brazil, Cameroon, Indonesia, Malaysia, and Ecuador [ 19 ]. The compositional profile of the triacylglycerols (TAGs) of CB considerably varies with the origin of the plant, season of collection of the beans, variety of the tree, and handling techniques during the extraction process [ 20 ]. Commonly found triacylglycerols (TAGs) in CB include glycerol-1-palmitate-2-oleate-3-stearate (POSt; P-palmitic, St-stearic, O-oleic; 33.7–40.5%), glycerol-1,3-distearate-2-oleate (StOSt; 23.8–31.2%), and glycerol-1,3-dipalmitate-2-oleate (POP; 13.6–15.5%) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%